Manajemen Pendidikan Islam Perspektif Kiai Muh. As’ad Umar - Bakri Bakri; M. Ansor Anwar (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2018)
This research set out of an existing view of Indonesian people that Islamic education has lower interest than public school. This phenomenon reveals question to be answered that why it happened. Perhaps it was caused by the elevation of Islamic education problems such as management crisis. It is common knowledge that Islamic education still uses traditional management. Thus, it inspires the writer to carry out the research about Islamic education management based on KH Muh As’ad’s point of view. It aims to describe Islamic management education paradigm and Islamic leaders thinking on the education; to explain Islamic management education based on KH Muh As’ad Umar Point of view; to prove the superiority Islamic education management of Kh. Muh. As’ad Umar. This research applied qualitative approach with observation method, interview, and documentation such as classical book, journal and Islamic leader opinion. While, the secondary data were article, magazine and writing which discuss about Islamic education management. It applied also empirical approach to specify the research into case study. The case study is an attempt conducted intensively, detailed and in-depth on a particular object. Research results show that organization management of Kiai As’ad held collectively, the rights and obligations are the same but the duties and authority vary according to their field; KH Asad Umar has been acted as innovator, motivator, communicator, and the mover of developing Islamic institution; KH Asad Umar has the ability to communicate and implement the vision well and right and enable to succeed manager role in creating a commitment to the values of Islam in education management. A recommendation from a this research is how educators, Islamic educational institutions headmaster and all education practitioners are able to further enhance the knowledge of Islamic education management, including the management of education based on Islam.